Cumulative sum analysis of the learning curve for the preclosure technique using Proglide. (26th October 2019) - Gao, Haoyu; Luo, Mingyao; Fang, Kun; Fan, Bowen; Zhao, Jiawei; Xue, Yunfei; Shu, Chang
Abstract: OBJECTIVES: Our study aims to assess the technical quality and the learning curve of the preclosure technique for a vascular surgeon using Proglide using cumulative sum analysis (CUSUM analysis). METHODS: This study was designed retrospectively and enrolled 81 consecutive patients with 88 access sites who underwent endovascular aortic repair or thoracic endovascular aortic repair with the preclosure technique using Proglide between July 2017 and February 2018. The patients were divided into 2 groups chronologically: (A) the first 40 cases and (B) the latter 41 cases. Logistic regression analysis was used to assess the impact of technical risk factors on the success of the preclosure technique, and the χ 2 test and 1-way ANOVA were applied to analyse the distribution of individual characteristics and risk factors between the 2 groups. CUSUM analysis was adapted to analyse the learning curve and to monitor the technical quality, with a predetermined target failure rate of 5%, an alternative failure rate of 20% and calculated 80% 'alert', 95% 'alarm' and 80% 'reassurance' lines. RESULTS: Primary technical success was obtained in 81 (92.05%) access sites. There were no significant correlations between primary technical success and risk factors, including, common femoral artery diameter ( P  = 0.88), common femoral artery depth from the skin ( P  =0.94), the level of common femoral artery calcification ( P  =0.86) and size of sheath ( P  =0.96). Moreover, the distribution of related risk factors was not significantly different between groups A and B. CUSUM analysis showed that the cumulative failure rate never crossed the 80% 'alert' and 95% 'alarm' lines. Additionally, the failure rate began to approach the 80% 'reassurance' line after ∼22 cases and crossed the 80% 'reassurance' line after 36 cases. CONCLUSIONS: The technique of totally percutaneous access using Proglide is safe and effective for an experienced vascular surgeon, even if the operator has no previous experience with any preclosure techniques. CUSUM analysis showed that 36 cases are necessary to achieve the target failure rate of 5%.